Application of Bamboo Shoot Liquid Fertilizer and Time of Pruning on Peanut Production (Arachis hypogaea L.) - Rifqy, Ahmad Alfian Maulana; Rr. Liliek Dwi Soelaksini (KHD Production, 2025)
The decreasing trend in peanut productivity in Indonesia over the years is primarily linked to soil degradation resulting from the overuse of synthetic fertilizers. Therefore, it is necessary to apply environmentally friendly methods such as liquid organic fertilizer and pruning to optimize peanut productivity. This research aimed to examine the influence of bamboo shoot liquid fertilizer and pruning time on peanut production. The research was conducted in Antirogo Villcommunity age, Sumbersancy during the period from July to October 2024. Using a Randomized Block Design with two factors. The first factor was the concentration of bamboo shoots liquid fertilizer namely P0 (0 ml/L), P1 (100 ml/L), and P2 (200 ml/L). The second factor was W0 (shoot pruning time which consisted of control), W1 (7 days after flowering), and W2 (14 days after flowering). The results imply that the results indicated that the concentration of bamboo shoots liquid fertilizer of 100 ml/L has a significant effa notable example fresh shoot weight per-sampel. In addition, the shoot pruning treatment conducted 7 days after flowering had a notable effect on the fresh pod weight per-sample. Based on the interaction between the two factors, it has an effect on fresh pod weight per sample, dry pod weight per sample, dry seed weight per sample, and dry seed weight per plot.